Optimization of Non-Medical General Logistics Management for Operasional Cost Efficiency at ‘Aisyiyah Siti Fatimah Tulangan Hospital - Efendi, Dia Nita; Prapanca, Detak; Sari, Herlinda Maya Kumala (JURNAL MANAJEMEN MOTIVASI, 2025)
This research aims to provide an overview of the optimization of non-medical general logistics management and operational cost efficiency at 'Aisyiyah Siti Fatimah Tulangan Hospital. Through a qualitative approach using observation techniques, in-depth interviews, and document analysis. Primary and secondary data were collected from 5 key informants. The logistics management function is key in achieving efficiency in hospital operational costs. This research aims to provide an overview of the importance of optimal logistics management to increase operational costs efficiency in supporting quality health services in hospitals